1989
DOI: 10.1073/pnas.86.1.312
|View full text |Cite
|
Sign up to set email alerts
|

Detection of serum hepatitis B virus DNA in patients with chronic hepatitis using the polymerase chain reaction assay.

Abstract: We compared the sensitivity of the polymerase chain-reaction (PCR) assay to that of slot-blot hybridization for detecting hepatitis B virus (HBV) DNA in the serum of 31 patients with chronic hepatitis. Of 14 chronic hepatitis patients positive for both HBV surface and HBV e antigens, 9 were positive for HBV DNA by slot-blot hybridization and all 14 by PCR. Also, of 9 patients positive for HBV surface antigen and antibody against HBV e antigen, 2 were positive for HBV DNA by slot-blot analysis and 8 by PCR. Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
103
3

Year Published

1992
1992
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(116 citation statements)
references
References 16 publications
10
103
3
Order By: Relevance
“…Nested PCR was carried out as described by Kaneko et al 23 , with some modifications. The S region was amplified according to a standard technique 24 for identification of the HBV genotype.…”
Section: Individual Levelmentioning
confidence: 99%
“…Nested PCR was carried out as described by Kaneko et al 23 , with some modifications. The S region was amplified according to a standard technique 24 for identification of the HBV genotype.…”
Section: Individual Levelmentioning
confidence: 99%
“…Conversely, it was believed for several years that patients who had cleared HBeAg and seroconverted to anti-HBe positivity were noninfectious. Clinical studies in which HBV DNA was detected in HBsAg-positive patients with anti-HBe, initially by hybridization and in subsequent studies by PCR, demonstrated that a proportion of HBsAg-positive patients who clear HBeAg still show signs of replicative infection (14). Carman et al (9) put forward a molecular explanation for this.…”
mentioning
confidence: 99%
“…This might be due to the high number of HBsAg particles but lack of HBV in the sera [5]. Another reason for this finding would be that the blood samples from the corresponding patients would have been obtained in the latter rather than early phases of chronic HBV carriage where the levels of HBV DNA are likely to be Brief report low in the serum due to clearance by the immune system resulting in negative PCR [6].…”
Section: Discussionmentioning
confidence: 97%